Methane conversion to liquid hydrocarbons over ga-hzsm-5 zeolite catalyst / Asmadi Ali … [et al.] - Ali, Asmadi; Ibrahim, Mohd Zamri; Awang, Mohamad; Norsani, Wan Mohd; Mat, Ramli (2002)
The HZSM-5 zeolite catalyst was modified by an acidic ion exchange method to produce the Ga-HZSM-5 zeolite catalyst. The effects of different reaction temperatures on the catalytic activity of Ga-HZSM-5 catalyst were studied. Catalytic testing was carried out in a micro packed bed reactor where the catalyst was placed in a stainless steel tube reactor supported by glass wool. The direct oxidation of methane was carried out at reaction temperature, under atmospheric pressure, and 9 vol. % of O2 in the feed. The catalytic activity was tested with six different reaction temperatures. The liquid and gas products were analyzed by gas chromatography. In the range studied, the optimum reaction temperature to produce the highest yield of liquid hydrocarbons was observed at 800°C.